Landscape and Earth in Early Modernity : Picturing Unruly Nature. - Göttler, Christine; Mochizuki, Mia. (Bielefeld : Amsterdam University Press, 2022)
Early modern views of nature and the earth upended the depiction of land. Landscape emerged as a site of artistic exploration at a time when environments and ecologies were reshaped and transformed. This volume historicizes the contingency of an ever-changing elemental world, reframing and reimagining landscape as a mediating space in the interplay between the natural and the artificial, the real and the imaginary, the internal and the external. The lens of the "unruly" reveals the latent landscapes that undergirded their conception, the elemental resources that resurfaced from the bowels of the earth, the staged topographies that unsettled the boundaries between nature and technology, and the fragile ecologies that undermined the status quo of human environs. Landscape and Earth in Early Modernity: Picturing Unruly Nature argues for an art history attentive to the vicissitudes of circumstance and attributes the regrounding of representation during a transitional age to the unquiet landscape.
Frontmatter -- Table of Contents -- List of Illustrations -- Acknowledgments -- Landscape, Mutability, and the Unruly Earth: An Introduction -- Part 1. Latent Landscapes -- 1. Waterland and the Disquiet of the Dutch Landscape -- 2. Landscape and Autography -- 3. Painted Landscape before Landscape Painting in Early Modern England -- Part 2. Elemental Resources -- 4. Unruly Indigo? Plants, Plantations, and Partitions -- 5. A Natural History in Stone: Medusa's Unruly Gaze on bardiglio grigio -- 6. The Cosmologies of Early Modern Mining Landscapes -- Part 3. Staged Topographies -- 7. Aurea Aetas Antverpiensis : Land(scapes) in the Blijde Inkomst for Ernest of Austria into Antwerp, 1594 -- 8. An Overlooked Landscape Installation : The Winter Room at Copenhagen's Rosenborg Castle -- 9. Insidious Images: Veiled Sight and Insight in Pieter Bruegel's Landscapes -- Part 4. Fragile Ecologies -- 10. "In einem Augenblick": Leveling Landscapes in Seventeenth-Century Disaster Flap Prints -- 11. Performative Landscapes: A Paradigm for Mediating the Ecological Imperative? -- Index
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Landscapes in art; Nature in art; Paysages dans l'art.; Nature dans l'art.; Renaissance art; Early modern history: c 1450/1500 to c 1700.; ART / History / Renaissance; Landscapes in art; Nature in art; History of art; Landscapes / seascapes; European history: Renaissance; Art History, Early Modern, Landscape, Seascape, Nature